Chromium picolinate : - Passwater, Richard A. (Keats Pub., 1992)
Scientific research has shown startling muscle-building properties for chromium picolinate, without the dangerous side effects of steroids. Learn about this and the many other health-promoting aspects of this food supplement and how you can use it.